Lifetime prevalence of injuries in incoming division I collegiate football players. Issue 4 (2nd October 2017) - Sarac, Nikolas; Haynes, William; Pedroza, Angela; Kaeding, Christopher; Borchers, James
ABSTRACT: Objectives : The purpose of this study is to determine the lifetime prevalence of past injuries in incoming first year football players in a Division 1 college football team. Methods : Pre-participation questionnaires from 605 first-year football players over 20 years (1996–2015) were examined to determine the prevalence of concussions, stingers, fractures, and musculoskeletal surgeries sustained before playing at the collegiate level. Players were grouped by position: wide receiver and defensive back (WR/DB), offensive and defensive linemen (OL/DL), all other positions (OP), and unknown (UKN). Prevalence of injuries by year and position was compared using Pearson's χ 2 Test (p < 0.05). Results : The reported lifetime prevalence is as follows: concussion (21%), stinger (23%), musculoskeletal surgery (23%), and fracture (44%). There were no significant differences in lifetime prevalence of concussions (p = 0.49), stingers (p = 0.31), fractures (p = 0.60), or musculoskeletal surgeries (p = 0.97) based on position. There were also no significant differences in the lifetime prevalence of concussions (p = 0.14), musculoskeletal surgeries (p = 0.50), or fractures (p = 0.59) based on year. However, there was a significant difference in the lifetime prevalence of stingers based on year (p < 0.001). Conclusions : There was an expectation to observe an increase in injury prevalence by entering year, but this was not seen. A decrease in stingers was actually observed, but there was no significant difference among any other injury recorded. These results do not support the perception that football injuries are on the rise. Under reporting is a significant concern as players may fear disqualification or that they are evaluated by the coaching staff based on their medical history. More research is needed to confirm lifetime injury prevalence and evaluate differences over time among football players.